Can Spirituality Protect Medical Students from Psychological Distress? Evidence from a Descriptive-Analytical Study - Francisca A. Tjakradidjaja; Sophie Dwiyanti (Faculty of Medicine, UIN Syarif Hidayatullah Jakarta, 2025)
Background: Heightened psychological distress is commonly reported among medical students due to academic pressure, multiple assessments, disrupted sleep, and a competitive learning environment. This study investigates the role of spirituality as a potential protective factor for mental health among first-year medical students. Methods: A descriptive-analytical design was employed, involving 115 students who completed a demographic questionnaire, the Daily Spiritual Experiences Scale (DSE), and the General Health Questionnaire-12 (GHQ-12). Results: A total of 92 valid responses were obtained, resulting in an 80% response rate. Respondents were predominantly female (n = 61, 66.3%), with most aged 18 years (n = 59, 64.1%). Regarding Qur’anic memorization, 43.5% had memorized only a few short chapters, 40.2% had memorized 1-5 juz, and 4.3% had memorized 26-30 juz. Mental health screening indicated that 46.7% had a positive mental state, while 53.3% were categorized as having a negative mental state. Notably, 80.4% of students (n = 74) reported limited levels of spirituality. Statistical analysis revealed a strong positive correlation between spirituality and mental health (r = 0.99; p = 0.00). Conclusion: These findings suggest that higher spiritual engagement may buffer psychological distress and that integrating spiritual approaches into medical education could help mitigate psychological distress in early training stages.